2004
DOI: 10.1038/sj.ijir.3901250
|View full text |Cite
|
Sign up to set email alerts
|

Sexual problems among women and men aged 40–80 y: prevalence and correlates identified in the Global Study of Sexual Attitudes and Behaviors

Abstract: The Global Study of Sexual Attitudes and Behaviors (GSSAB) is an international survey of various aspects of sex and relationships among adults aged 40-80 y. An analysis of GSSAB data was performed to estimate the prevalence and correlates of sexual problems in 13 882 women and 13 618 men from 29 countries. The overall response rate was modest; however, the estimates of prevalence of sexual problems are comparable with published values. Several factors consistently elevated the likelihood of sexual problems. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

68
861
11
51

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,215 publications
(1,010 citation statements)
references
References 33 publications
68
861
11
51
Order By: Relevance
“…The GSSAB study reported the global prevalence of PE (based on subject self-report) to be approximately 30% across all age groups. 15,16 Similar results by age groups were also reported by the Brazilian Sexual Life Study: PE was reported in 25.8% of 3332 Brazilian men. 17 JaspersenGastelum et al 18 reported a high prevalence rate in older age groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The GSSAB study reported the global prevalence of PE (based on subject self-report) to be approximately 30% across all age groups. 15,16 Similar results by age groups were also reported by the Brazilian Sexual Life Study: PE was reported in 25.8% of 3332 Brazilian men. 17 JaspersenGastelum et al 18 reported a high prevalence rate in older age groups.…”
Section: Discussionsupporting
confidence: 84%
“…Data from the Global Study of Sexual Attitudes and Behaviors (GSSAB), an international survey investigating the attitudes, behaviors, beliefs and sexual satisfaction of 27 500 men and women aged 40 --80 years, reported that the global prevalence of PE (based on subject self-report) is approximately 30% across all age groups. 15,16 Many studies have found age to be a predisposing factor for EjD. EjD increases with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…It further showed a high rate of hesitancy in seeking help because of economic and sociocultural considerations [2]. Numerous studies from diverse geographic and sociocultural backgrounds have suggested similar problems globally [1, 3, 4, 5, 6, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Around 43% of American women have been found to suffer from FSD [1]. A multicenter, multination study of Asian women revealed sexual problems in the range of 20–25%.…”
Section: Introductionmentioning
confidence: 99%
“…51 Patients suffering from ED may ejaculate soon after erection and before the failure-to-maintain phase of the erection sets in. 52 Some experiments have shown a relationship between ejaculation function and PDE-5.…”
Section: Pde-5ismentioning
confidence: 99%